2015
DOI: 10.1021/ml500497s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Quinazolines as Inhibitors of the Bacterial Cell Division Protein FtsZ

Abstract: The bacterial cell division protein FtsZ is one of many potential targets for the development of novel antibiotics. Recently, zantrin Z3 was shown to be a cross-species inhibitor of FtsZ; however, its specific interactions with the protein are still unknown. Herein we report the synthesis of analogues that contain a more tractable core structure and an analogue with single-digit micromolar inhibition of FtsZ's GTPase activity, which represents the most potent inhibitor of Escherichia coli FtsZ reported to date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Based on zantrin Z3(1), a known GTPase inhibitor of Bs- FtsZ (IC 50 24 μM), 77 Nepomuceno et al synthesized several quinazoline analogs as inhibitors of FtsZ and their potency examined. 77 Compound ZZ3(2), the N,N -dimethyl analog of ZZ3(1), was found to be twice as potent as ZZ3(1) (IC 50 12 μM).…”
Section: Ftsz Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on zantrin Z3(1), a known GTPase inhibitor of Bs- FtsZ (IC 50 24 μM), 77 Nepomuceno et al synthesized several quinazoline analogs as inhibitors of FtsZ and their potency examined. 77 Compound ZZ3(2), the N,N -dimethyl analog of ZZ3(1), was found to be twice as potent as ZZ3(1) (IC 50 12 μM).…”
Section: Ftsz Inhibitorsmentioning
confidence: 99%
“…77 Compound ZZ3(2), the N,N -dimethyl analog of ZZ3(1), was found to be twice as potent as ZZ3(1) (IC 50 12 μM). Further SAR study revealed that benzo[g]quinazoline of ZZ3(1) and ZZ3(2) could be replaced by a smaller quinazoline, bearing an ammonium salt side chain, to form the most active compound 10 in this series (IC 50 9 μM).…”
Section: Ftsz Inhibitorsmentioning
confidence: 99%
“…The chlorination of 1 with thionyl chloride was followed by reaction with aqueous ammonia to give 3-hydroxybenzamide (2) in a good yield. The alkylation of 2 with alkyl chloride or bromide (sodium iodide was not needed for the reaction with alkyl bromide) in the presence of sodium iodide and potassium carbonate afforded 3-O-alkylbenzamide derivatives (4)(5)(6)(7)(8) in 57-63% yields. Similarly, the alkylation of 2 with phenylalkyl chloride or bromide provided 3-O-arylalkylbenzamide subjected to deprotection of ethoxymethyl group to afford 3-hydroxy-2,6-difluorobenzamide (31) in good yield.…”
Section: Resultsmentioning
confidence: 99%
“…The SAR study discovered that benzo[g]quinazoline of Zantrin Z3 could be substituted by a smaller quinazoline while the 4-chlorostyryl moiety was critical for inhibitory effect on GTPase activity of FtsZ. Among these analogs, 39 (in Figure 6) having an ammonium salt side chain shows the best potency against GTPase of FtsZ with an IC 50 of 9 μM [113]. …”
Section: Quinazoline Derivativesmentioning
confidence: 99%